Peran Mutasi Gen BRCA1 dan BRCA2 dalam Deteksi Dini dan Prediksi Risiko Kanker Payudara: Tinjauan Genetika Molekuler - Kirana, Yulisia Rezky; Riakurnaini; Rachmawaty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Germline pathogenic variants in BRCA1 and BRCA2 are key determinants of Hereditary Breast and Ovarian Cancer (HBOC) and substantially increase breast cancer risk. At the molecular level, BRCA1/2 dysfunction impairs homologous recombination repair (HRR) of double-strand breaks (DSBs), promoting genomic instability and carcinogenesis. This systematic review synthesizes evidence on how BRCA1/2 variants inform early detection and clinical risk prediction/stratification in breast cancer. A PRISMA 2020-guided Systematic Literature Review was conducted using Scopus (2022–2026; MEDI/BIOC; English; Open Access; article type). Of 232 records identified, 21 articles met inclusion criteria and were synthesized narratively across five themes: molecular mechanisms, risk/penetrance, early detection, risk prediction/stratification, and clinical implications/targeted therapy. The evidence indicates that HRR deficiency shifts DNA repair toward more error-prone pathways, while carrier risk remains heterogeneous due to additional genetic modifiers and polygenic risk scores (PRS), resulting in meaningful variation in absolute risk. Early detection in BRCA carriers emphasizes genetic testing for carrier identification and intensified surveillance, with breast MRI as a key modality in high-risk settings. Contemporary risk models increasingly integrate BRCA status, PRS, and clinical factors, although population-specific calibration remains critical to avoid biased risk estimates. Clinically, DNA repair deficiency supports the use of PARP inhibitors (PARPi) via synthetic lethality, with resistance dynamics warranting consideration. Overall, BRCA-informed strategies provide an essential foundation for genetics-based prevention, screening, risk prediction, and targeted therapy in breast cancer.